2017
DOI: 10.1007/s12031-017-0998-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CLIP3 Upregulation on Astrocyte Proliferation and Subsequent Glial Scar Formation in the Rat Spinal Cord via STAT3 Pathway After Injury

Abstract: Spinal cord injury (SCI) is a devastating event resulting in neuron degeneration and permanent paralysis through inflammatory cytokine overproduction and glial scar formation. Presently, the endogenous molecular mechanisms coordinating glial scar formation in the injured spinal cord remain elusive. Signal transducer and activator of transcription 3 (STAT3) is a well-known transcription factor particularly involving in cell proliferation and inflammation in the lesion site following SCI. Meanwhile, CAP-Gly doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…NSE expression and activity are frequently increased in neuronal and glial activation and injury, major factors implicated in neurodegenerative diseases [ 71 , 72 ]. In neuronal degeneration, glial cells regulate neuronal metabolism to support stressed neurons.…”
Section: Nse In Neuronal and Glial Cell Activation Differentiatiomentioning
confidence: 99%
See 1 more Smart Citation
“…NSE expression and activity are frequently increased in neuronal and glial activation and injury, major factors implicated in neurodegenerative diseases [ 71 , 72 ]. In neuronal degeneration, glial cells regulate neuronal metabolism to support stressed neurons.…”
Section: Nse In Neuronal and Glial Cell Activation Differentiatiomentioning
confidence: 99%
“…Increased NSE expression and activity may also drive metabolic changes that take place in regions away from the epicenter in injured spinal cord. Secondary insult in SCI is characterized by destruction of neuronal and glial cells that leads to the expansion of the damage and loss of function [ 72 ]. Thus, mechanisms that either promote or prevent neuronal inflammation and cell death could be investigated to find new avenues for preventing and treating neurodegenerative disorders.…”
Section: Nse In Neurodegeneration and Neuroprotectionmentioning
confidence: 99%
“…An earlier study reported a link between increased lactate dehydrogenase and improved intracellular NSE expression in neurotoxin-exposed cells (Thomas et al, 1991). The production and function of NSE in glial activation is enhanced, with major factors involved in neurodegenerative diseases (Chen et al, 2018;Zabel and Kirsch, 2013). PFC and hippocampus Immunohistochemical analysis showed an increase in the expression of the NSE, though not statistically significant when qualitatively examined.…”
Section: Discussionmentioning
confidence: 97%
“…Kazuma and colleagues had earlier reported that AA restored behavioural deficit in addition to depleting amyloid plaques in a mouse model of AD, and attributed their findings to decreases CNS oxidative damage mediated by AA (Murakami et al, 2011). AA has been reported to protect against apoptosis by regulating the modulation of the mitochondrial pathway of cytochrome C activities that resulted in the altered release of lactate dehydrogenase (Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…FRK played a role in pancreatic cancer cells migration and proliferation, and was suggested to be critical therapeutic targets of pancreatic cancer [49]. CLIP3 was shown as anti-in ammatory regulator involved in TNF-α signaling [50] and also attributed to injury recovery [51], while it was a novel target in cancer predicted in the crosstalk gene network. CECR2 functions with SMARCA1 in CERF complex (CECR2-containing remodeling factor) to regulate cell differentiation and development [52].…”
Section: Discussionmentioning
confidence: 99%